2012
DOI: 10.22230/cjnser.2012v3n2a121
|View full text |Cite
|
Sign up to set email alerts
|

Community Development to Feed the Family in Northern Manitoba Communities: Evaluating Food Activities based on Their Food Sovereignty, Food Security, and Sustainable Livelihood Outcomes

Abstract: This article explores food-related activities and their impacts on sustainable livelihood assets, food sovereignty, and food security, and provides insight for future food-related community development. Analysis is based on community food assessments conducted in 14 Northern Manitoba communities and included a food security survey, price survey, and interviews. The lack of community control over development in First Nation and other Northern remote and rural communities in Northern Manitoba is found to undermi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
65
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 18 publications
(9 reference statements)
0
65
0
2
Order By: Relevance
“…Par exemple, une étude de 2012 sur 14 collectivités du nord du Manitoba a révélé que les trois quarts des ménages (75 %) étaient en situation d'insécurité ali mentaire. L'incidence et la gravité de l'insécurité alimentaire étaient variables, avec des taux généralement plus élevés dans les collectivités accessibles unique ment par avion que dans celles accessibles par la route ou par chemin de fer 12 . De même, d'après une étude menée en 2013 sur la Première nation de Fort Albany, établie le long de la côte de la baie James dans ce qui constitue aujourd'hui le nord de l'Ontario, 70 % des ménages vivaient dans l'insécurité alimentaire 13 .…”
Section: Contexteunclassified
See 1 more Smart Citation
“…Par exemple, une étude de 2012 sur 14 collectivités du nord du Manitoba a révélé que les trois quarts des ménages (75 %) étaient en situation d'insécurité ali mentaire. L'incidence et la gravité de l'insécurité alimentaire étaient variables, avec des taux généralement plus élevés dans les collectivités accessibles unique ment par avion que dans celles accessibles par la route ou par chemin de fer 12 . De même, d'après une étude menée en 2013 sur la Première nation de Fort Albany, établie le long de la côte de la baie James dans ce qui constitue aujourd'hui le nord de l'Ontario, 70 % des ménages vivaient dans l'insécurité alimentaire 13 .…”
Section: Contexteunclassified
“…58 . Parmi les solutions à l'insécurité alimen taire, notons un accès facilité pour les peu ples autochtones aux aliments terrestres et marins grâce à des réseaux communau taires de partage d'aliments, des pro grammes d'aide à la récolte et à la chasse et par l'utilisation de congélateurs commu nautaires 4,12,16 . Autrement dit, la souve raineté alimentaire des Autochtones est indispensable à la décolonisation des envi ronnements alimentaires locaux.…”
Section: Contexteunclassified
“…The incidence and severity of food insecurity varied, with fly-in communities generally having more severe and higher rates of food insecurity than those with road or train access. 12 Similarly, a 2013 study in Fort Albany First Nation, located along the James Bay coast in present-day northern Ontario, found that 70% of households suffered from food insecurity. 13 Both works note that the retail environments of fly-in First Nations have limited options, and that lack of access to all-weather roads has an enormous impact on food security.…”
Section: Introductionmentioning
confidence: 98%
“…13 Both works note that the retail environments of fly-in First Nations have limited options, and that lack of access to all-weather roads has an enormous impact on food security. 12 The largest and most common retailer in First Nations communities in the provincial Norths is the North West Company (NWC). Also known as the Northern Store, the NWC has a long history in these communities as the former Northern Department of the Hudson's Bay Company (HBC).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation